Intra‐operative application of ultrasonography (USG) for reduction of zygomatic arch fracture. Issue 11 (11th November 2021) - Acharya, Pradeep; Dongol, Ashok; Yadav, Anjani Kumar; Bhattarai, Nilima; Jaisani, Mehul Rajesh
Abstract: Zygomatic arch fractures are the most common facial fractures or second in frequency after the nasal fractures. The high incidence of zygomatic fractures probably relates to its prominent position in the facial skeleton; hence, it is frequently exposed to fractures. This case report presents an left‐sided isolated zygomatic arch fracture after subjected to routine investigations and radiographs like submentovertex and CT scans. The patient was operated under general anesthesia for the reduction of zygomatic arch by Gille's temporal approach with the use of Ultrasound intra‐operatively. Recommendation for the use of ultrasonography in the identification of zygomatic arch fractures intra‐operatively operatively. Abstract : Ultrasonogram can be considered as the imaging of choice when there is a contraindication to CT or conventional radiograph by reducing the overall amount of radiation. Which also can be the another treatment modalities for the surgical management of close reduction of zygomatic arch fracture.